ダイ37ジ ナンキョク チイキ カンソクタイ フユタイ ホウコク 1996-1997 - 藤井, 理行; フジイ, ヨシユキ; 川田, 邦夫; カワダ, クニオ; Fujii, Yoshiyuki; Kawada, Kunio (1999)
P(論文) 第37次南極地域観測隊越冬隊は40名で構成され, 昭和基地とドームふじ観測拠点で越冬した。昭和基地では, 31名が1996年2月1日から1997年1月31日まで, 基地の運営・維持管理にあたるとともに, 定常観測と研究観測を実施し, ほぼ所期の目的通りの成果を得た。越冬中の6月, 倉庫棟の設備工事が終了し運用を始めた。10月には, 積雪による電源ケーブルたわみに起因する小火やピラタス機の雪面接触事故が起きたが, 幸い人身事故には至らなかった。ドームふじ観測拠点では, 9名が1996年1月23日から1997年1月25日まで越冬をし, 越冬隊の主要な観測課題であった氷床深層掘削を行い, 12月に所期の目標を超える2503mの深度に達した。基地の運営や維持管理, 気象や雪氷, 医学の研究観測も行われ成果を得た。 The wintering party of the 37th Japanese Antarctic Research Expedition (JARE-37) executed its planned activities at Syowa and Dome Fuji Stations from 1996 to 1997. The wintering party at Syowa Station, consisting of 31 personnel, carried out its observations and logistic work from 1 February 1996 to 31 January 1997. Some specific observations were conducted for studies on upper atmospheric physics, atmospheric science, solid earth geophysics, biology and medical science as well as routine observations. Besides the station observations at Syowa, airborne and field observations were carried out for air sampling, geomagnetic measurement, ice sheet margin monitoring, penguin population monitoring and so on. The second wintering at Dome Fuji Station started from 23 January 1996 and was completed on 25 January 1997. The wintering party, consisting of 9 personnel, conducted deep ice core drilling to a depth of 2503m succesfully and performed in-situ core analyses. Routine meteorological and glaciological observations were carried out at the station. A few day field trips were carried out for radio echo sounding of the ice sheet in the summit area. departmental bulletin paper